1991
DOI: 10.1088/0029-5515/31/3/008
|View full text |Cite
|
Sign up to set email alerts
|

Second harmonic electron cyclotron heating of lower hybrid current driven plasma in JFT-2M

Abstract: Second harmonic electron cyclotron heating for the extraordinary mode in lower hybrid current driven plasma has been investigated experimentally in the JFT-2M tokamak. Effective electron heating is observed at largely downshifted cyclotron frequencies as well as at the usual cyclotron resonance frequency. An absorption efficiency of 15% at f0/2fc0 = 0.76 is estimated from measurements of the Shafranov parameter and the diamagnetic flux (f0 is the frequency of the RF wave and fc0 is the cyclotron frequency at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…This property, hereafter called the synergy effect, has been subsequently confirmed by a different Fokker-Planck code [10], by a self-consistent kinetic-transport code [11], and by analytical calculations [12]. The above-mentioned experiments [3][4][5][6][7][8] have shown that EC waves could couple to the fast electron tail sustained by LH waves and thus provide efficient current ramp-up, despite the fact that in most cases the EC waves absorption took place after multiple reflections on the tokamak walls. However, it is well known [1] that the physics of current ramp-up is dominated by the inductive response of the plasma, i.e., the transient reverse electric field, and not simply by the kinetic balance of quasilinear wave diffusion and Coulomb collisions.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This property, hereafter called the synergy effect, has been subsequently confirmed by a different Fokker-Planck code [10], by a self-consistent kinetic-transport code [11], and by analytical calculations [12]. The above-mentioned experiments [3][4][5][6][7][8] have shown that EC waves could couple to the fast electron tail sustained by LH waves and thus provide efficient current ramp-up, despite the fact that in most cases the EC waves absorption took place after multiple reflections on the tokamak walls. However, it is well known [1] that the physics of current ramp-up is dominated by the inductive response of the plasma, i.e., the transient reverse electric field, and not simply by the kinetic balance of quasilinear wave diffusion and Coulomb collisions.…”
mentioning
confidence: 95%
“…LH waves can efficiently drive electrons from low to substantially higher parallel velocities, making them poorly collisional and insensitive to trapping, thus carrying a larger current than the slower electrons interacting with the EC waves. For these reasons, the idea of combining the two CD systems has been proposed and investigated since the early 1980s [2] and has stimulated dedicated experiments on the WT-2 [3,4], JFT-2M [5,6], and WT-3 [7,8] tokamaks. Moreover, kinetic calculations [9] performed with a 3D Fokker-Planck code have numerically demonstrated an interesting property: the current driven by the simultaneous use of the two waves, I LHEC , can be significantly larger than the sum of the currents separately driven by the two waves, I LH I EC , in the same plasma conditions.…”
mentioning
confidence: 99%
“…However, the occurrence of optically thin phases in a discharge, as well as the finite k ʈ spectrum admitted by any real antenna, result in possible signal "pollution" in the presence of suprathermal electrons. 91 It should be noted that the other standard temperature diagnostic technique in high-temperature plasmas, Thomson scattering, is also perturbed by nonthermal electrons in a manner defined by the instrumental spectral response function. 92,93 It has recently been proposed that the discrepancies between ECE and Thomson-scattering measurements could themselves be exploited to diagnose the suprathermal population, 94 although the approach appears difficult and has not seen any concrete applications to date.…”
Section: F501-5mentioning
confidence: 99%
“…1986; Kawashima et al. 1991; Maehara et al. 1998) have shown that EC waves could couple to the fast electron tail sustained by LH waves.…”
Section: Introductionmentioning
confidence: 99%
“…Runaway production was also observed to be enhanced in LHCD with IBW in several kinds of target plasmas in the HT-7 tokamak (Chen et al 2008). Experiments (Ando et al 1986;Kawashima et al 1991;Maehara et al 1998) have shown that EC waves could couple to the fast electron tail sustained by LH waves. Since runaways represent a serious threat to tokamak vessel structures when they impinge on the vessel wall or plasma facing components, the avoidance of runaway electrons is one of the outstanding problems of the tokamak fusion reactor, especially during disruptions (Esposito et al 2003).…”
Section: Introductionmentioning
confidence: 99%